Thermal and chemical modification of wood – a combined approach for exclusive, high-demanding performance products. Issue 1 (2nd January 2023) - Goli, Giacomo; Negro, Federico; Emmerich, Lukas; Militz, Holger
ABSTRACT: Chemical and thermo-chemical modification processes were applied to European beech wood to make it applicable for interior applications which place high demands on aesthetics, hygrothermal and water resistance performance. In particular, the use of modified wood in kitchen tools was foreseen. Impregnation modification with a 20% DMDHEU solution, thermal modification and a combined approach of thermo-chemical modification were compared. All modification processes caused a darkening that for the high modification intensities became close to the aesthetics of some of the most renowned tropical hardwood species. The higher the modification intensity, the higher the improvement. In particular, chemical and thermo-chemical modification processes significantly decreased the liquid water uptake. As regards the mechanical performances while stiffness and strength did not change abruptly and hardness increased, the resistance towards dynamic impacts significantly decreased with every kind of modification process. Thermo-chemical modifications resulted to be an interesting way to improve most of the physical properties of wood with outstanding behaviour in terms of colour appearance and reduction of water uptake in wet environments. An increased brittleness is the weakest point for foreseen fields of application.